The Impact of Network Human Capital on Economic Growth of Supply Chain in Digital Economy - S.A. Dyatlov; Ð¢.Ð. Selishcheva; G.F. Feigin; I.V. Borodushko; D.V. Gilmanov (International Journal of Supply Chain Management, 2018)
Abstract- The article reveals the features of the neural-network technological revolution and digital economy development. They substantiate the proposition that in the modern digital economy new informational-network properties and the competences of highly skilled workers are developed and human capital is transformed into network human capital. The definition of